Extending More than One Week the Shelf Life of Fresh-Cut Lettuce Using Vinegar Enriched in Bioactive Compounds Encapsulated in α-Cyclodextrins - María de los Ángeles Martínez-Sánchez; Ginés Benito Martínez-Hernández; Antonio López-Gómez (Foods)
Fresh-cut salads are highly appreciated by consumers due to their healthy and convenient nature. Fresh-cut (FC) lettuce is one of the best-selling FC products due to its freshness and low preparation time for salads. However, FC lettuce is very perishable and, in addition, has been recently associated with severe foodborne illness alerts. Alternative natural sanitizing treatments to conventional sodium hypochlorite are needed. The antimicrobial activity of vinegar has been well-known since ancient times. In addition, bioactive compounds from plant byproducts are widely recognized for their antioxidant properties. This work aimed to evaluate the use of a novel and encapsulated vinegar powder enriched with bioactive compounds from fruit byproducts with high antimicrobial and antioxidant properties to preserve the physicochemical (titratable acidity, total soluble solids, weight loss, and color), microbial (psychrophiles, enterobacteria, lactic-acid bacteria, molds, and yeasts), and sensory quality of FC lettuce at 4 °C for up to 10 days. Small to no differences were observed in terms of physicochemical quality (≈0.1% titratable acidity; 2.3–3.3% total soluble solids; <1% weight loss) in comparison to control samples through storage. Vinegar treatments reduced by 2–4 log CFU g−1 the microbial loads after 10 days. In addition, a synergistic sensory antibrowning effect (greener and less yellowish appearance, showing −a* and −b*) between organic acids and the released polyphenols from the encapsulated plant byproduct extracts was observed. Hence, the enriched encapsulated vinegar represents an effective green alternative to conventional sanitizers to maintain the quality of FC lettuce through storage time.